Validity and reliability of the Indonesian version of Physical Activity Questionnaire for adolescents (PAQ-A) and older children (PAQ-C) - Andriyani, Fitria Dwi; Indra, Eka Novita; Priambadha, Aprida Agung; Monnaatsie, Malebogo (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2024)
Existing study examining the validity and reliability of the Physical Activity Questionnaire for adolescents (PAQ-A) in Indonesian youth did not explain whether it conducted cross-cultural adaptation to the questionnaire or not, and the authors did not publish the Indonesian version of the questionnaire. None of the previous studies investigated the validity and reliability of the Indonesian version of PAQ-C. This study aimed to conduct a cross-cultural adaptation of PAQ-A and PAQ-C into the Indonesian language (Bahasa Indonesia) and to check its validity and reliability. This research employed a cross-sectional design. Two groups were recruited: grade 5 students (n=58, 10-12 years old) and grade 7 students (n=61, 13-15 years old). The concurrent validity was verified against the Indonesia Physical Fitness Test (IPFT). We also investigated the item validity and inter-item correlations. The reliability was tested by using the Cronbach Alpha technique. Results showed that the concurrent validity of the Indonesian version of PAQ-A and PAQ-C against IPFT are low (rho= 0.224 and rho= 0.165, consecutively) (p>0.05). The item validity of the Indonesian version of PAQ-A ranged between 0.338 and 0.737; while for PAQ-C ranged between 0.329 – 0.818. Inter-item correlation for PAQ-A and PAQ-C ranged from -0.019 to 0.569 and 0.000 to 0.704, respectively. The reliability of the Indonesian version of PAQ-A and PAQ-C is acceptable (Î± = 0.740 and Î± = 0.705 – 0.712, consecutively). In conclusion, we found that the item validity of PAQ-A and PAQ-C were at a moderate level. The validity of the PAQ-A and PAQ-C were lower when they were checked against a physical fitness test, comparable to previous studies with device-based measurements. The Indonesian version of PAQ-A and PAQ-C have a moderate level of reliability. Our results suggest that the use of the questionnaires will be better complemented by other device-based measurements, such as accelerometers or pedometers.